2018
DOI: 10.18488/journal.aefr.2018.87.925.945
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Behavior and Capital Structure Decisions; Do Overconfidence, Optimism and Risk Aversion Matter?

Abstract: G4 This study aims at examining the importance of managers' behavior in explaining the capital structure related decisions of the listed firms in the Egyptian stock exchange (EGX). Managers' behavior data has been collected using a survey method (i.e. psychometric test) which specifies three aspects of the behavior (namely: overconfidence, optimism, and risk aversion) in addition to some demographic characteristics as suggested by previous studies particularly Graham et al. (2013) and Menkhoff et al. (2006). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
0
17
0
2
Order By: Relevance
“…Cain and McKeon (2016) used US federal pilot license records to measure risk appetite and found that pilot CEOs tend to take more risks as evidenced by higher leverage and pronounced stock market return volatility. CEOs' risk preferences also impact leverage decisions, and those with longer tenure show stronger patterns (Abdeldayem and Sedeek, 2018;Carvalho and Cerejeira, 2019). Supporting evidence also shows a negative relationship between a CEO's risk aversion and volatility in an enterprise's earnings, implying that more conservative CEOs are inclined to smooth volatility in a firm's profits (Abdel-Khalik, 2007).…”
Section: Managerial Risk Appetitementioning
confidence: 99%
“…Cain and McKeon (2016) used US federal pilot license records to measure risk appetite and found that pilot CEOs tend to take more risks as evidenced by higher leverage and pronounced stock market return volatility. CEOs' risk preferences also impact leverage decisions, and those with longer tenure show stronger patterns (Abdeldayem and Sedeek, 2018;Carvalho and Cerejeira, 2019). Supporting evidence also shows a negative relationship between a CEO's risk aversion and volatility in an enterprise's earnings, implying that more conservative CEOs are inclined to smooth volatility in a firm's profits (Abdel-Khalik, 2007).…”
Section: Managerial Risk Appetitementioning
confidence: 99%
“…Heifetzy and Spiegel (2001), Germain et al (2005) and Barone-Adesi et al (2012) undertook substantial research on optimism as a heuristic bias within the context of financial economics. Optimism (pessimism) is among the greatest influencing biases-being principally driven and guided by past returns, it has direct impacts on investors' return expectations, return tolerance and risk perceptions (Hoffmann & Post, 2012) and significantly influences capital structure decisions (Abdeldayem & Sedeek, 2018).…”
Section: Optimismmentioning
confidence: 99%
“…The finance literature defines optimism bias as the overestimation of the probability of positive events and the underestimation of the probability of negative events (Abdeldayem & Sedeek, 2018). This bias can be noticed in managers who constantly seek debt financing for their companies (Antonczyk & Salzmann, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%